Value-Added Analysis of the Dried Fish Manufacturing Industry in Bengkulu City - Melysa Nabilasari; Bambang Sumantri; Sriyoto Sriyoto (Journal of Global Sustainable Agriculture, 2022)
Dried fish is a processing fishery product carried out traditionally and simply with the help of sunlight. This fish processing is carried out to add value to fish and fishery products. This study aims to analyze the amount of added value of the dried fish-making business in Bengkulu City. This research was conducted from January to February 2022 in Sumber Jaya Village, Kampung Melayu District, Bengkulu City. The sample of this study was 86 people selected using the census method, where the entire population was sampled. The data used are primary and secondary, and the data analysis used is a quantitative analysis using the Hayami method. The results showed that the business of making dried fish in Bengkulu City could create added value because it had an NT value of >0 (positive). The amount of added value for each type of fish used is Rp. 5,799.32/kg (beleberan), Rp. 4,223.61/kg (case), Rp. 5,161.32/kg (beledang), Rp. 7,556.13/kg (kerong), and Rp. 9,592.77/kg (stone nutmeg)